Violation of the regulation of cytokine in chronic catarrhal gingivitis in overweight children - Kostura, Viktoria; Bezvushko, Elvira; Musij-Sementsiv, Khrystyna (Journal of Medical Science, 2017)
Introduction. The development of inflammation in the periodontium is inextricably linked to the system processes in the organism, including an accompanying pathology, which is often parallel. The WHO particularly emphasizes the dissemination of overweight among children. Against the background of excessive weight gain in children there are the series metabolic disorders that provoke chronic diseases, including chronic catarrhal gingivitis.Aim. The aim of this study was to identify the dynamics of cytokines (IL-4, IL-6) in oral fluid and characterize the immune system of the oral cavity in children with overweight and obesity.Material and Methods. This study presents the results of examination of 80 children with overweight and obese patients with chronic catarrhal gingivitis (CCG), aged 12–15 years. Based on anthropometric surveys body mass index (BMI) was calculated. Also the obtained measurements and calculations were evaluated by percentile tables that were designed by the WHO in 2007 for children and adolescents 5 to 19 years for both sexes separately (WHO, 2007). The content of interleukin (IL-4; IL-6) in oral fluid in children was determined by using kits of reagents of company "Vector-Best" (Russia), based on solid-phase "sandwich" variant of immunoenzyme analysis.Results. The level of IL-4 in the oral fluid of children with chronic catarrhal gingivitis decreases (1.8 times) with increasing of age and with the deepening of violations of fat metabolism. The level of IL-6 in the oral fluid of children with chronic catarrhal gingivitis increases (2.9 times) with increasing of age and the presence of excess body weight and obesity.Conclusions. Further study of interleukin imbalance in the oral fluid of patients with chronic catarrhal gingivitis and overweight is a promising area of research to develop methods of prevention and pathogenic therapy.
Keywords: cytokine; chronic catarrhal gingivitis; overweight children; oral fluid